The Effect of TiO2-SiO2 Nanocomposite as a Filler on the Self-Cleaning Properties of Material - Budi Utomo, Rohadi Satrio; Muflikhun, Muhammad Akhsin; Mukhtar Ariyadi, Hifni (Universitas Muhammadiyah Jember, 2024)
Implementation of TiO2-SiO2 nanocomposites has been a primary focus in the development of innovative materials. This research explores the potential application of TiO2-SiO2 nanocomposite as a filler in coating blends and 3D SLA resin. Achieving optimal self-cleaning properties is the main objective, considering the importance of a material's ability to cleanse itself from external dirt. The study employs the contact angle goniometer test to evaluate the hydrophobic properties of TiO2-SiO2 nanocomposite. The results indicate that samples containing TiO2-SiO2 nanocomposite as a filler exhibit a significant improvement in self-cleaning properties compared to control samples, as demonstrated by an increased contact angle between water and the sample material. This opens up opportunities for other applications, including efficient anti-corrosion coatings and 3D printing resin materials with self-cleaning properties, facilitating maintenance and enhancing the quality and durability of materials across various industrial sectors.